PERATURAN MAHKAMAH AGUNG DAN PERATURAN MAHKAMAH KONSTITUSI MENURUT JENIS PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Vica J. E. Saija (SASI, 2014)
The division of state power is divided into legislative power, executive power and judicial power. The task of government in carrying out public welfare within the meaning of the Constitution of the Republic of Indonesia Year 1945, in the implementation of needed legislation. Legislation in Indonesia is regulated in Law Number 12 Year 2011, the criteria used for such a legal instrument called a regulation regulations are written rules that contain legal norms binding in general and formed or defined by state agencies or officials authorized through the procedures laid down in Regulation Legislation. In Article 8 paragraph (2) one of the rules in the legislation recognized that Regulation of the Supreme Court and the Constitutional Court Regulation, then in this paper are analyzed on both the regulation which do not meet the criteria of legislation such as that contained in the Act No. 12 of 2011